Law and justice in the courts of classical Athens - Lanni, Adriaan 1972- (Cambridge University Press, 2006)
In this 2006 book, Adriaan Lanni draws on contemporary legal thinking to present a model of the legal system of classical Athens. She analyses the Athenians' preference in most cases for ad hoc, discretionary decision-making, as opposed to what moderns would call the rule of law. Lanni argues that the Athenians consciously employed different approaches to legal decision-making in different types of courts. The varied approaches to legal process stems from a deep tension in Athenian practice and thinking, between the demand for flexibility of legal interpretation consistent with the exercise of democratic power by ordinary Athenian jurors; and the demand for consistency and predictability in legal interpretation expected by litigants and necessary to permit citizens to conform their conduct to the law. Lanni presents classical Athens as a case study of a successful legal system that, by modern standards, had an extraordinarily individualised and discretionary approach to justice